Attenuation of HIV‐1 replication in macrophages by cannabinoid receptor 2 agonists. Issue 5 (1st May 2013) - Ramirez, Servio H.; Reichenbach, Nancy L.; Fan, Shongshan; Rom, Slava; Merkel, Steven F.; Wang, Xu; Ho, Wen‐zhe; Persidsky, Yuri
Abstract : CB2 expression is upregulated in HIV‐1 infected macrophages; CB2 agonists limits infection by inhibition of the HIV‐1‐LTR. Abstract : Infiltrating monocytes and macrophages play a crucial role in the progression of HIV‐1 infection in the CNS. Previous studies showed that activation of the CB2 can attenuate inflammatory responses and affect HIV‐1 infectivity in T cells and microglia. Here, we report that CB2 agonists can also act as immunomodulators on HIV‐1‐infected macrophages. First, our findings indicated the presence of elevated levels of CB2 expression on monocytes/macrophages in perivascular cuffs of postmortem HIV‐1 encephalitic cases. In vitro analysis by FACS of primary human monocytes revealed a step‐wise increase in CB2 surface expression in monocytes, MDMs, and HIV‐1‐infected MDMs. We next tested the notion that up‐regulation of CB2 may allow for the use of synthetic CB2 agonist to limit HIV‐1 infection. Two commercially available CB2 agonists, JWH133 and GP1a, and a resorcinol‐based CB2 agonist, O‐1966, were evaluated. Results from measurements of HIV‐1 RT activity in the culture media of 7 day‐infected cells showed a significant decrease in RT activity when the CB2 agonist was present. Furthermore, CB2 activation also partially inhibited the expression of HIV‐1 pol . CB2 agonists did not modulate surface expression of CXCR4 or CCR5 detected by FACS. We speculate that these findings indicate that prevention of viral entry is not a central mechanism for CB2 ‐mediated suppression in viral replication. However, CB2 may affect the HIV‐1 replication machinery. Results from a single‐round infection with the pseudotyped virus revealed a marked decrease in HIV‐1 LTR activation by the CB2 ligands. Together, these results indicate that CB2 may offer a means to limit HIV‐1 infection in macrophages.